التجربة الماليزية في التأمين التكافلي: دراسة تحليلية: (The Malaysian Experience in Islamic Insurance (Takaful): An Analytical Study) - فارس جعفري; محمد أكرم لال الدين (At-Tajdid - Intellectual Refereed Journal, 2022)
Abstract According to the Islamic financial services industry stability report published by IFSB in 2019, the takaful contributions in Southeast Asia were estimated to have reached US 3.86 billion in 2017, and Malaysia ranked first with total contributions of US 2.77 billion, which represented 70% of the total takaful contributions in Southeast Asia. In light of this, this paper examines the development of takaful industry at the global level, the emergence and development of the takaful industry in Malaysia, the contractual relationships governing the practice of takaful in Malaysia, and the main factors which make Malaysia as one of the pioneering models in takaful in Southeast Asia region. In terms of methodology, the research adopts a qualitative approach employing the inductive method to trace primary and secondary data on the topic and the descriptive method to describe the Malaysian experience in Islamic insurance. The research also adopts the analytical method to evaluate the viability of takaful in the Malaysian context. The study found that the developments of takaful in Malaysia are very promising due to the abundant encouragement provided by the regulators. The research has also concluded that the success of the Malaysian experience is due to the legal and regulatory frameworks, the infrastructure support system that facilitates and govern the work of takaful operators, and the healthy competitive environment among the takaful companies. These contributed to enhancing growth rate and making Malaysia a pioneering model in Islamic insurance in the Southeast Asia region. Keywords: Islamic insurance, takaful, legal framework, commitment to donate, Malaysia.